Test–Retest Reliability of Traditional and Inertial Measurement Unit-Derived Kinematic Variables During Three Functional Ankle Stability Tests Performed Using an Ankle Destabilization Device - Jeanne Dury; Gilles Ravier (International Journal of Athletic Therapy and Training, 2026)
Accurate and reliable assessment tools for detecting deficits in ankle control are still scarce. The purpose was to determine the reliability of kinematic variables derived from an inertial measurement unit added on an ankle destabilization device during the modified Star Excursion Balance Test, single-leg balance test, and Weight-Bearing Inversion Test. Angular velocity was the most reliable inertial measurement unit–derived variable during modified Star Excursion Balance Test (intraclass correlation coefficient = .67–.84) and Weight-Bearing Inversion Test (intraclass correlation coefficient = .91). In contrast to single-leg balance test, where mean ankle angulation showed good test–retest reliability (intraclass correlation coefficient = .79). Our results underline the value of combining ankle destabilization conditions and inertial measurement unit-derived variables in the assessment of ankle stability.